2016
DOI: 10.1093/gji/ggv529
|View full text |Cite
|
Sign up to set email alerts
|

Field observations of seismic velocity changes caused by shaking-induced damage and healing due to mesoscopic nonlinearity

Abstract: Korn, M. (2016): Field observations of seismic velocity changes caused by shaking-induced damage and healing due to mesoscopic nonlinearity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 66 publications
1
65
0
Order By: Relevance
“…Thermoelastic effects have been observed to dominate seasonal velocity changes in arid regions (Gassenmeier et al, 2016;Hillers et al, 2015;Richter et al, 2014). In the greater Los Angeles basin, which contains the SGV, Meier et al (2010) were not able to distinguish between seasonal variations due to hydrological or thermoelastic effects.…”
Section: 1029/2018gl077706mentioning
confidence: 93%
“…Thermoelastic effects have been observed to dominate seasonal velocity changes in arid regions (Gassenmeier et al, 2016;Hillers et al, 2015;Richter et al, 2014). In the greater Los Angeles basin, which contains the SGV, Meier et al (2010) were not able to distinguish between seasonal variations due to hydrological or thermoelastic effects.…”
Section: 1029/2018gl077706mentioning
confidence: 93%
“…Without necessarily interpreting the phases in the cross correlograms, one can also monitor the temporal evolution of the wave arrival times. AC and SC functions have been used to detect seismic velocity changes during earthquakes (Gassenmeier et al, 2016;Hobiger et al, 2012Hobiger et al, , 2014Hobiger et al, , 2016Richter et al, 2014;Wegler & Sens-Schönfelder, 2007) and volcanic eruptions (De Plaen et al, 2016). However, these studies focused on velocity changes of coda waves at relatively low frequencies (∼0.1 to 4 Hz), making the measurements sensitive to variations occurring within a few kilometers of depth.…”
Section: 1029/2018jb015697mentioning
confidence: 99%
“…In the past, most noise-based monitoring studies mainly focused on the changes in coseismic velocities (e.g., Chen et al, 2010;Takagi et al, 2012;Wegler et al, 2009;Wegler & Sens-Schönfelder, 2007;Yu & Hung, 2012;Zaccarelli et al, 2011). In recent years, we have seen a rapid increase in studies on the postseismic velocity changes or recovery of seismic velocity as a result of high-quality and long-term seismic observation (e.g., Gassenmeier et al, 2016;Hobiger et al, 2012Hobiger et al, , 2016Liu et al, 2014;Soldati et al, 2015;Taira et al, 2018;Ueno et al, 2012;Wu et al, 2016). Hobiger et al (2016) systematically studied the characteristics of seismic velocity recovery in different frequency bands of different earthquakes and found that the recovery time constant for all earthquakes was 0.55 years, wherein the coseismic velocity reduction is further divided into two sections: one is potential maximal recovery value, and the other is nonrecovery residual value, and the recovery time constant is defined as the time when the coseismic velocity drop recovers to a factor of 1/e of the maximal recovery value using an exponential fitting algorithm.…”
Section: Slow Postseismic Recovery: Slow Healing?mentioning
confidence: 99%